Respuesta :

Answer: Choice B

[tex]x^{1/8}y^{8}[/tex]

======================================================

Explanation:

The two rules we use are

[tex](a*b)^c = a^c*b^c[/tex]

[tex](a^b)^c = a^{b*c}[/tex]

When applying the first rule to the expression your teacher gave you, we can say that:

[tex]\left(x^{1/4}y^{16}\right)^{1/2} = \left(x^{1/4}\right)^{1/2}*\left(y^{16}\right)^{1/2}[/tex]

Then applying the second rule lets us say

[tex]\left(x^{1/4}\right)^{1/2}*\left(y^{16}\right)^{1/2} = x^{1/4*1/2}*y^{16*1/2} = x^{1/8}y^{8}[/tex]

Therefore,

[tex]\left(x^{1/4}y^{16}\right)^{1/2} = x^{1/8}y^{8}[/tex]

-------------

In short, we just multiplied each exponent inside by the outer exponent 1/2.

So that explains why the exponents go from {1/4,16} to {1/8,8} for x and y in that exact order.